Solution‐dispersed CuO nanoparticles as anode buffer layer in inverted type hybrid organic solar cells. Issue 1 (16th September 2016) - Sabri, Nasehah Syamin; Yap, Chi Chin; Yahaya, Muhammad; Mat Salleh, Muhamad; Hj Jumali, Mohammad Hafizuddin
Abstract : A solution‐dispersed copper oxide (CuO) nanoparticles anode buffer layer has been investigated to improve the efficiency of inverted type hybrid organic solar cell (OSC) based on zinc oxide (ZnO)/poly(3‐hexylthiophene) (P3HT) with and without an electron acceptor, (6, 6)‐phenyl‐C61‐butyric acid methyl ester (PCBM). The photoactive layer consisted of P3HT was spin‐coated onto the ZnO nanorod arrays that were grown on fluorine tin oxide (FTO) substrate. The CuO nanopowders dissolved in 1‐butanol, ethanol, and 1‐propanol were then spin‐coated onto the photoactive layer, followed by the deposition of silver (Ag) using thermal evaporation technique. The contact angle measurements indicate that CuO nanopowders dispersed in 1‐butanol showed the highest wettability on the photoactive layer surface, which results in better photovoltaic performance compared to the other solvents (ethanol and 1‐propanol). For further investigation, the CuO anode buffer layer spin coating speed dependence of inverted type hybrid OSC based on ZnO/P3HT:PCBM was also studied. The CuO layer deposition on top of photoactive layer was optimized by using various spin coating speeds of 1000, 2000, and 3000 rpm. The optimum PCE of 2.24% was achieved at a spin coating speed of 2000 rpm, as a result of uniform and complete coverage of CuO on the photoactive layer.